Parque educativo y cívico infantil, el espacio como educador y transformador social (2022)
In recent decades, Colombia has made great efforts in the education of children throughout the country. Educational architecture plays an important role in these efforts to improve education, however, there is a key problem and that is the implementation of new infrastructure with the same traditional methodologies of the industrial revolution. The objective of this project is to contribute to the improvement of education in communities that have suffered from the armed conflict based on their needs, the application of new methodologies that focus on children from 5 to 11 years of age and that respond to the challenges of the future generations; For the realization, different educational models in the world were analyzed, especially the models of the Nordic countries that are based on the development of society from equality regardless of age, economic situation or gender.